Membangun Budaya Organisasi Positif: Manajemen Lingkungan Internal Sekolah - Sheptea Mardhiyah Putri; Neyna Fakhira Salsabila; Muhammad Akmal Firdaus; Hesti Kusumaningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
This article examines the importance of building a good organizational culture within school internal administration framework. It aims to investigate efficient methods for building and maintaining an organizational culture that supports student and educator growth. Through an in-depth literature review, several key elements are identified, including visionary leadership, shared vision-mission formulation, and staff empowerment. The article emphasizes the importance of creating a cooperative work environment to foster innovation and creativity. Key aspects examined include learning-supportive physical space design, positive psychological atmosphere creation, reward systems, and conflict management strategies. The research also discusses main obstacles such as resistance to change and generational differences, while presenting practical solutions to address them. In conclusion, building a good organizational culture is an ongoing effort requiring dedication from all parties involved. This research provides important perspectives for education practitioners and policymakers in improving overall educational standards.